Current Practice of Logbook-based Internship Programme in Undergraduate Medical Education of Bangladesh: Intern Doctors’ Views (Bangladesh Journal of Medical Education, 2023)
Background: The medical internship of Bangladesh is designed supervised training programme for newly graduate medical doctors to gain necessary knowledge, skills, attitudes, ethics necessary to identify, analyze and manage clinical problems in order to provide effective, efficient and competent patient care independently in future.Methods: This cross-sectional descriptive study was conducted from 01 July 2021 to 30 June 2022 upon 400 intern doctors to get their views administering a self-administered structured questionnaire about current practice of the logbook-based internship programme in undergraduate medical education of Bangladesh.Results: The study found that mean sores of interns by their agreement about initiation of their internship, the process of their internship, achievement of competency during their internship and methods of the training during their internship were above 4 out of 5 point Liker scale.Conclusion: The logbook-based internship programme in undergraduate medical education of Bangladesh were going very satisfactory.Bangladesh Journal of Medical Education Vol.14(1) January 2023: 35-42